Epidemiological investigation of a foodborne outbreak in Lebanon caused by vibrio parahaemolyticus. (c2018) - Fattel, Leila F. (2018)
Vibrio parahaemolyticus is a halophilic, Gram-negative, marine bacterium. It is found inhabiting as part of the microbiota in aquatic animals, especially shellfish, and is non-pathogenic but can cause acute hepatopancreatic necrosis in shrimps in the presence of two toxins PirAVP and PirBVP. An unconventional V. parahaemolyticus strain has been linked to disorders in humans too. Upon consumption of contaminated seafood, the virulent strain causes gastroenteritis through hemolysins, such as tdh, trh, and tlh. V. parahaemolyticus is still generally susceptible to various groups of antibacterial drugs, however, its resistance to blactams was previously detected. A pandemic strain of V. parahaemolyticus belonging to serotype O3:K6 is responsible for most of the clinical outbreaks worldwide. The pandemic spread of this strain was correlated to the acquisition of orf8 via a bacteriophage, leading to an increase in virulence. In addition, pathogenicity islands and mobile elements contributed to the evolution of the O3:K6 serotype. In this study, V. parahaemolyticus was collected from the Middle East Institute of Health University Hospital in Lebanon. The isolates were analyzed and compared using whole-genome sequencing. Virulence was tested by the detection of hemolysins tdh, trh, and tlh. Resistance was analyzed by antibiotic susceptibility testing and the performance of PCRs for b-lactamases, and quinolone resistance determinants. Genetic relatedness of the isolates was studied by multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and whole genome-based SNP analysis (wgSNP). All of the isolates had the tdh+, trh-, GS-PCR+ genotype, which is a characteristic of the O3:K6 pandemic clone. The isolates were resistant to ampicillin (100%), ceftazidime (86%), ticarcillin (14%), and amikacin (14%). All of the isolates belonged to ST3 and had very similar phylogenetic fingerprints. The isolates undertaken in this study exhibited almost identical resistance, virulence, and phylogenetic patterns, indicating an outbreak linked to the spread of the pandemic O3:K6 serotype in the country.